The Role of Zero Waste Learning Classes in Shaping Environmental Behavioral Change and Collective Identity - Nurul Hidayah; Mohammad Masykuri; Feti Fatimatuzzahroh (Environmental Pollution Journal, 2026)
This study analyzes the role of the Zero Waste Learning Class (Kelas Belajar Zero Waste/BZW) in shaping environmental behavior change and collective identity through community-based environmental education. A qualitative phenomenological approach was employed to explore the lived experiences of 14 BZW alumni as part of a grassroots sustainability movement. Data were collected through in-depth interviews, participant observation, and analysis of community documents, and analyzed using thematic analysis guided by the Theory of Planned Behavior, Maslow’s Hierarchy of Needs, and Collective Identity Theory. The findings show that participation in BZW promotes gradual and sustained pro-environmental behavior change, influenced by positive attitudes toward zero waste practices, strengthened community social norms, and increased perceived behavioral control through practical learning processes. This process also fosters a shift in motivation and values from individual concern to collective ecological responsibility. The study concludes that the Zero Waste Learning Class functions as a transformative learning environment that contributes to the development of ecological citizenship at the community level.